STRATEGIS SISTEM INFORMASI PADA UNIVERSITAS XYZ JOMBANG MENGGUNAKAN FRAMEWORK WARD AND PEPPARD DAN PORTOFOLIO MCFARLAN STRATEGIC GRID - Nanang Junaedi (Politeknik Sawunggalih Aji, 2017)
An agency must have had a development plan in running the organization. Careful planning will make useful improvements in each section . Strategic planning information system created as a reference organized and in line with the vision and mission , so that the institution's goals can be achieved correctly . In this study , the authors formulate a strategic plan for the system in which the information can be used as a tool to support the success of XYZ University in achieving the vision and mission and goals of the institution. The method used is based on the thought of John Ward and Joe Peppard and strategic planning analysis methods using McFarlan Strategic Grid portfolio analysis to formulate the information system to support the agency's performance in the future . Keywords : Strategic Planning , Strategic Information Systems , Ward and Peppard , McFarlan Strategic Grid .